The search for stability: bar displacement in three series of pectus excavatum patients treated with the Nuss technique - Tedde, Miguel Lia (2011)
OBJECTIVES: To compare bar displacement and complication rates in three retrospective series of patients operated on by the same surgical team. METHOD: A retrospective medical chart analysis of the three patient series was performed. In the first series, the original, unmodified Nuss technique was performed. In the second, we used the ''third point fixation'' technique,and in the last series, the correction was performed with modifications to the stabilizer and stabilizer position. RESULTS: There were no deaths in any of the series. Minor complications occurred in six (4.9%) patients: pneumothorax with spontaneous resolution (2), suture site infection (2), and bar displacement without the reoperation need (2). Major complications were observed in eight (6.5%) patients: pleural effusion requiring drainage (1), foreign body reaction to the bar (1), pneumonia and shock septic (1), cardiac perforation (1), skin erosion/seroma (1), and displacement that necessitated a second operation to remove the bar within the 30 days of implantation (3). All major complications occurred in the first and second series. CONCLUSION: The elimination of fixation wires, the use of shorter bars and redesigned stabilizers placed in a more medial position results in a better outcome for pectus excavatum patients treated with the Nuss technique. With bar displacement and instability no longer significant postoperative risks, the Nuss technique should be considered among the available options for the surgical correction of pectus excavatum in pediatric patients.